Tocotrienols Modulate a Life or Death Decision in Cancers - Tham, Shiau-Ying (Int J Mol Sci, 2019)
Malignancy often arises from sophisticated defects in the intricate molecular mechanisms of cells, rendering a complicated molecular ground to effectively target cancers. Resistance toward cell death and enhancement of cell survival are the common adaptations in cancer due to its infinite proliferative capacity. Existing cancer treatment strategies that target a single molecular pathway or cancer hallmark fail to fully resolve the problem. Hence, multitargeted anticancer agents that can concurrently target cell death and survival pathways are seen as a promising alternative to treat cancer. Tocotrienols, a minor constituent of the vitamin E family that have previously been reported to induce various cell death mechanisms and target several key survival pathways, could be an effective anticancer agent. This review puts forward the potential application of tocotrienols as an anticancer treatment from a perspective of influencing the life or death decision of cancer cells. The cell death mechanisms elicited by tocotrienols, particularly apoptosis and autophagy, are highlighted. The influences of several cell survival signaling pathways in shaping cancer cell death, particularly NF-κB, PI3K/Akt, MAPK, and Wnt, are also reviewed. This review may stimulate further mechanistic researches and foster clinical applications of tocotrienols via rational drug designs.